KONSUMSI DAGING SEBAGAI INDIKATOR ANEMIA PADA WANITA USIA SUBUR - Prihatini, Sri; Kartika, Vita; Sari, Yunita Diana (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Background: In the future nutrition surveilans will be developed not only for macro nutrient problem but also for micro nutrient. Anaemic is still one of main nutrition problems in Indonesia. About 27% of women of reproductive age and 48% of under-fives are anemic problem. One of the caused of high prevalenceanemic in Indonesia was low level of iron consumption on daily meals. Therefore, it is required cheap, easy and sensitive indicator for anemic surveillans. Objectives: To studies the possibility meat consumption as an anaemic indicator on woman of reproductive age. Methods: Research design is cros-sectional, which conducted in Bali and Banten province. The subjects are women of reproductive age (WORA) aged 17-40 years old. A total number of 576 WORA was selected by simple random sampling. Data collected are food consumption by using Semi Quantitative Questioner Food Frequency (FFQ), socio economic, parity, family planning, food supplement, anthropometric and Haemoglobine level. Data were analysis by logistic regression and reliability test. Results: Logistic regression analysis showed that meat consumption less than twice for a week associated with increased of the risk of anemic by 2.2 times compared with women with twice for a week or more. Parity three times or more, increased risk of anemic by 2.85 times compared with women with paruty less than three times. Furthermore, the reliability test indicates that consumption of meats less than twice a week as indicator of anemia has sensitivity 76.6% and specificity 46.1% Conclusions: Meat consumption less than twice a week can not use as indicator for anaemia among woman at reproductive age. [Penel Gizi Makan 2009, 32(2): 112-121] Keywords: indicator, meat consumption, anemia